LncRNAs regulate the cyclic growth and development of hair follicles in Dorper sheep - Sun, Haoran; Meng, Ke; Wang, Yifan; Wang, Yayan; Yuan, Xiaochun; Li, Xinhai (Frontiers in Veterinary Science, 2023)
Abstract: Hair follicles in Dorper sheep are characterized by seasonal cyclic growth and development, consequently resulting in hair shedding during spring. The cyclic growth and development of hair follicles are regulated by several influencing factors such as photoperiods, hormones, age of the animal, genes, long non-coding RNAs (lncRNAs), and signaling pathways. In the present study, skin samples of five shedding sheep (S), used as experimental animals, and three non-shedding sheep (N), used as controls, were collected at three time points (September 27, 2019; January 3, 2020; and March 17, 2020) for RNA sequencing (RNA-seq) technology. Nine different groups (S1-vs-S2, S1-vs-S3, S2-vs-S3, N1-vs-N2, N1-vs-N3, N2-vs-N3, S1-vs-N1, S2-vs-N2, and S3-vs-N3) were compared using FDR < 0.05 and |log2FC|>1 as thresholds to assess the differences in the expression of lncRNAs. In total, 395 differentially expressed (DE) lncRNAs were screened. Cluster heatmap analysis identified two types of expression patterns, namely, high expression during the anagen phase (A pattern) and high expression during the telogen phase (T pattern). Gene Ontology (GO) enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses revealed that the target genes were largely enriched in the Estrogen signaling pathway, PI3K-Akt signaling pathway, Fc gamma R-mediated phagocytosis, and cell adhesion molecules (CAMs), which are associated with hair follicle cyclic growth and development-related pathways. In addition, 17 pairs of lncRNAs-target genes related to hair follicle cyclic growth and development were screened, and a regulatory network was constructed. Altogether, candidate lncRNAs and their regulated target genes were screened that contributed to sheep hair follicle cyclic growth and development. We believe these findings will provide useful insights into the underlying regulatory mechanisms.